Effects of epicardial versus transvenous left ventricular lead placement on left ventricular function and cardiac perfusion in cardiac resynchronization therapy: A randomized clinical trial. (14th June 2017) - van Dijk, Vincent F.; Fanggiday, Jim; Balt, Jippe C.; Wijffels, Maurits C.E.F.; Daeter, Edgar J.; Kelder, Johannes C.; Boersma, Lucas V.A.
Abstract: Introduction: Optimal left ventricular (LV) lead position in patients undergoing cardiac resynchronization therapy (CRT) is crucial to achieve an optimal effect on hemodynamics. Due to various difficulties, up to 30% of transvenous LV lead placements fail, or a suboptimal position is achieved. Surgical epicardial LV lead placement could be performed at a position anticipated to be the optimal site. This could have a more favorable effect, which may be expressed by increased improvement in left ventricular ejection fraction (LVEF) and cardiac perfusion. The objective of this trial is to compare transvenous versus epicardial LV lead placement in CRT in a randomized fashion Methods and results: Fifty‐two patients were randomized to either epicardial or transvenous approach. All patients received an ICD with CRT. Patients were followed for 6 months after device implant. Primary endpoint was the degree of change in cardiac perfusion measured by myocardial perfusion scintigraphy. LVEF equally improved in both groups, from 24% to 36% in the transvenous group versus 25% to 35% in the epicardial group (P = 0.797). Cardiac perfusion, expressed as summed stress score, improved in both groups without a significant difference as well (P = 0.727). Complication rate was similar, respectively 6 and 7 patients had any complication. Admission time was significantly longer in the epicardial group with 2 (2–7) versus 3 (2–32) days (P <0.001). Conclusion: Epicardial LV lead placement does not result in additional improvement of LVF or myocardial perfusion compared to the conventional transvenous in CRT.